1996
DOI: 10.1001/archpsyc.1996.01830020055007
|View full text |Cite
|
Sign up to set email alerts
|

Increased Number of Vasopressin- and Oxytocin-Expressing Neurons in the Paraventricular Nucleus of the Hypothalamus in Depression

Abstract: The AVP and OXT neurons were activated in the PVN in patients with major depression or bipolar disorder. This activation may be associated with activation of the hypothalamic-pituitary-adrenal axis in these patients, since both AVP and OXT are known to potentiate the effects of corticotropin-releasing hormone. Because of their central effects, activation of AVP and OXT neurons may also be related to symptoms of major depression or bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
190
1
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(204 citation statements)
references
References 61 publications
7
190
1
6
Order By: Relevance
“…This altered feedback might be involved in adaptive changes described post mortem in the hypothalamic CRH and AVP neurons that control the pituitary-adrenocortical system (Purba et al 1996). Thus, the HAB animals may represent a promising model for further investigation of the psychopathological significance of a dysregulated HPA system.…”
Section: Involvement Of Glucocorticoid and Mineralocorticoid Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…This altered feedback might be involved in adaptive changes described post mortem in the hypothalamic CRH and AVP neurons that control the pituitary-adrenocortical system (Purba et al 1996). Thus, the HAB animals may represent a promising model for further investigation of the psychopathological significance of a dysregulated HPA system.…”
Section: Involvement Of Glucocorticoid and Mineralocorticoid Receptorsmentioning
confidence: 99%
“…Thus, the hypothalamic signal for ACTH secretion produced by the parvocellular CRH neurons gradually shifts from a CRH-dominated signal to a more AVP-dominated one . Indeed, Purba et al (1996) found indications of an enhanced vasopressinergic drive by showing an increased number of AVP-expressing neurons in the PVN of depressed patients. Although the findings so far are not consistent (Heuser et al 1998), additional indirect evidence for a role of AVP in affective disorders comes from the finding that fluoxetine treatment leads to a reduction in cerebrospinal fluid concentrations of AVP in patients with major depression (de Bellis et al 1993).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies found an increased AVP concentration in the cerebrospinal fluid (De Bellis et al, 1993, Heuser et al, 1998 and in the plasma (van Londen et al, 1997, van Londen et al, 1998, de Kloet et al, 2008 of depressive subjects, especially in suicide victims (Inder et al, 1997, Brunner et al, 2002. Postmortem studies have found an elevated number of AVP-expressing neurons, increased AVP level in the PVN (Purba et al, 1996, Merali et al, 2006 and an enhanced AVP mRNA You created this PDF from an application that is not licensed to print to novaPDF printer (http://www.novapdf.com) in the SON (Meynen et al, 2006). Additionally, a single nucleotide polymorphism of the AVP V1b receptor has been found to protect against major depression (van West et al, 2004).…”
mentioning
confidence: 99%